Experimental study on progressive collapse resistance of corroded RC continuous deep flexural members - Bao, Chao; Long, Huan; Ma, Xiaotong; Alshaikh, Ibrahim M.H.; Al-Mekhlafi, Galal; Peng, Luyuan; Wang, Huxiang (Elsevier Ltd., 2025)
Abnormal loads can induce localized damage, potentially triggering the progressive collapse of reinforced concrete (RC) structures, leading to casualty and severe economic loss. In coastal or high-salinity environments, harsh conditions accelerate structural degradation, compromising resistance to progressive collapse, primarily due to reinforcing bar corrosion caused by chloride infiltration. To investigate the impact of corrosive environments on the progressive collapse resistance of RC continuous deep flexural members, quasi-static testing was conducted on four scaled-down RC substructure specimens. Besides one control group specimen, the remaining three specimens underwent electrochemically accelerated corrosion at 3%, 9%, and 12% across the entire specimen area, respectively. Failure modes and internal force were analyzed and compared. The results show that damage in both corroded and uncorroded specimens was concentrated in the plastic hinge regions near the beam ends. Reinforcing bar corrosion significantly affected the compression arch mechanism and the catenary mechanism, reducing the bearing capacities of these two mechanisms by up to 12.0% and 16.0%, respectively.